2019
DOI: 10.1007/s00127-019-01672-3
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic position and suicidal behaviour in rural Sri Lanka: a prospective cohort study of 168,000+ people

Abstract: Purpose Lower socioeconomic position (SEP) is associated with an increased risk of suicidal behaviour in high income countries, but this association is not established in low- and middle-income countries (LMIC). Methods We investigated the association of SEP with suicidal behaviour in a prospective cohort study of 168,771 Sri Lankans followed up for episodes of attempted suicide and suicide. SEP data were collected at baseline at the household and individual level at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
0
8
0
1
Order By: Relevance
“…Nearly two-thirds of the Sri Lankan work force are part of the informal economy: these individuals are likely to be hardest hit by the negative impact of the pandemic on the national economy as it is a group that is already at highest risk of suicide and self-harm. 36 Support for these individuals must continue and be increased as needed to prevent suicide and self-harm.…”
Section: Discussionmentioning
confidence: 99%
“…Nearly two-thirds of the Sri Lankan work force are part of the informal economy: these individuals are likely to be hardest hit by the negative impact of the pandemic on the national economy as it is a group that is already at highest risk of suicide and self-harm. 36 Support for these individuals must continue and be increased as needed to prevent suicide and self-harm.…”
Section: Discussionmentioning
confidence: 99%
“…While most studies did not find any association, three studies (from India, Indonesia, and Pakistan) found that people who died by suicide were more likely to be unemployed. A more recent large scale cohort study from Sri Lanka ( 33 ) also did not identify association between unemployment and suicidal behavior; however, they found that people from lower socioeconomic positions (e.g., daily wage laborers) had higher risk of suicidal behavior.…”
Section: Resultsmentioning
confidence: 91%
“…There are likely differences in the societal and cultural impact of economic factors (e.g., unemployment) on suicidal behaviors, as well as variation in the needs and capacity of governments and organizations in responding to these impacts. The few systematic reviews and cohort studies in LMICs across Asia ( 32 , 33 ) suggest the associations between unemployment and suicidal behavior are less clear cut.…”
Section: Discussionmentioning
confidence: 99%
“…As situações sociais e econômicas podem interferir nas predisposições para o surgimento do comportamento suicida incluindo as tentativas de suicídio 10 e suicídio 11 , entre elas estão pessoas que passaram por experiências como problemas financeiros, acadêmicos ou relacionados ao trabalho, que sofreram algum tipo de discriminação, trauma ou abuso, dentre outros. Aspectos relacionados à violência como o abuso sexual contra mulheres também pode estar associado a um aumento de tentativas e do suicídio 12 .…”
Section: Aheah Of Printunclassified